2014
DOI: 10.1103/physrevb.89.085203
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study of magnetic linear dichroism and birefringence in (Ga,Mn)As

Abstract: Magnetic linear dichroism and birefringence in (Ga,Mn)As epitaxial layers is investigated by measuring the polarization plane rotation of reflected linearly polarized light when magnetization lies in the plane of the sample. We report on the spectral dependence of the rotation and ellipticity angles in a broad energy range of 0.12-2.7 eV for a series of optimized samples covering a wide range on Mn dopings and Curie temperatures and find a clear blueshift of the dominant peak at energy exceeding the host mater… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 70 publications
2
34
0
Order By: Relevance
“…For realistic material parameters, the Kerr angle is found to be of the order of 10 −1 radian for optical frequencies below 10 14 Hz. This is 'giant' compared to the usually observed values of 10 −6 − 10 −4 radians in topological insulators, magnetic and other materials 46,55,57,58 . For light incident on the surface with Fermi arc states (parallel to the node separation), we find that Θ Kerr ∝ σ yz /σ zz = 0.…”
Section: Introductionmentioning
confidence: 73%
“…For realistic material parameters, the Kerr angle is found to be of the order of 10 −1 radian for optical frequencies below 10 14 Hz. This is 'giant' compared to the usually observed values of 10 −6 − 10 −4 radians in topological insulators, magnetic and other materials 46,55,57,58 . For light incident on the surface with Fermi arc states (parallel to the node separation), we find that Θ Kerr ∝ σ yz /σ zz = 0.…”
Section: Introductionmentioning
confidence: 73%
“…The generation of spin may become less effective at higher photon energies due to increased spin relaxation. In this wavelength regime, the circular dichroism increases monotonically with wavelength [22], further ruling out circular dichroism as the dominant source of the helicity dependent term. The helicity dependent direction of DW motion is observed for the experimentally accessible temperatures of 85-98 K.…”
Section: H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 92%
“…To exclude the possible extrinsic response, the initial reference phase of the lock-in amplifier was fixed during the entire measurement. Since the MLD effect is sensitive to the density of states in the vicinity of the Fermi level of the measured magnetic sample, we set the photon energy to 1.58eV (i.e., near the energy gap of (Ga,Mn)As) so as to maximize the amplitude of the MLD signal [16,18,19]. It is now well established that the compressively-strained (Ga,Mn)As layer as used in our experiment is characterized by an in-plane biaxial magnetocrystalline anisotropy with easy axes along [100]…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it has been reported that the three-dimensional magnetization precession trajectory excited by a laser pulse can be reconstructed by disentangling the out-of-plane and the in-plane projections of the magnetization based on magnetic linear dichroism (MLD)and on the polar Kerr effect (PKE) in ferromagnetic (Ga,Mn)As [16][17][18]. The strong in-plane magneto-optical effect in this material makes the giant MLD a powerful technique for studying hole-mediated ferromagnetism via the quantitative measurement of magnetization precession [19]. Besides, MLD can also serve as an efficient experimental tool for investigating materials'…”
Section: Introductionmentioning
confidence: 99%